2017
DOI: 10.1016/j.exger.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery as a stressor and the response of the vulnerable older adult

Abstract: In an aging population, recovery and restoration of function are critical to maintaining independence. Over the past 50 years, there have been dramatic improvements made in cardiac surgery processes and outcomes that allow for procedures to be performed on an increasingly older population with the goal of improving function. Although improved function is possible, major surgical procedures are associated with substantial stress, which can severely impact outcomes. Past literature has identified that frail pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 91 publications
0
27
0
7
Order By: Relevance
“…Meta-analytic data based on nine prospective studies showed that an improvement in gait rate by 0.1 m/s leads to a 10% improvement in survival (Afilalo et al, 2014). Patients' dependence with respect to basic vital functions or the use of auxiliary devices are independent predictors of test results after cardiac surgeries (Neupane et al, 2017).…”
Section: Determinants Reduction In Physical Activitymentioning
confidence: 99%
“…Meta-analytic data based on nine prospective studies showed that an improvement in gait rate by 0.1 m/s leads to a 10% improvement in survival (Afilalo et al, 2014). Patients' dependence with respect to basic vital functions or the use of auxiliary devices are independent predictors of test results after cardiac surgeries (Neupane et al, 2017).…”
Section: Determinants Reduction In Physical Activitymentioning
confidence: 99%
“…The literature has largely focused on the biological or physical aspects of frailty as a risk factor; however, more recently there is greater appreciation for the psychologic and social aspects of frailty, which may also result in negative postoperative outcomes. 7,8 Chronologic age is inextricably linked to frailty but should not be the sole determinant in determining operative vulnerability or assignment of treatment futility. Younger patients can also be frail.…”
Section: What Is Frailty and Is It A Risk Predictor In Cardiac Surgery?mentioning
confidence: 99%
“…Many of the previous studies conducted on physical frailty and cognitive impairment focus only on adults aged 65 years and older. 9,12,27,28 More than half (69.2%) of the physically frail and cognitively impaired patients in our cohort were aged 65 years or older. This is consistent with previous literature that the risk of cognitive and physical decline increases exponentially with age.…”
Section: Discussionmentioning
confidence: 96%
“…However, surgery is a complex process that is not only a physical stressor, but also a mental stressor. 9 Many recent studies have considered incorporating the concept of cognition in the definition of frailty, 1012 and a definition for cognitive frailty has emerged. In 2013, an International Consensus Group 13 on cognitive frailty was organized to propose a heterogeneous clinical manifestation characterized by the simultaneous presence of both physical frailty and cognitive impairment in the elderly.…”
mentioning
confidence: 99%